Investigating the Impact of CSR Practices on Financial Performance: A Multiple Mediation Analysis in the Moroccan Exporting SMEs - Lagoubi, Sara; Balhadj, Said (Jordan Journal of Business Administration, 2024)
Numerous pieces of research have shown that corporate social responsibility (CSR) orientation is key to driving long-term survival, growth and sustainable performance in a complex and dynamic environment. However, studies of the relationship between CSR and financial performance (FP) have yielded disparate results. Therefore, the current study aims to examine the effect of CSR on FP by using customer satisfaction (CS), reputation (REP) and competitive advantage (CA) as mediating variables. The data for this study was collected via a survey of 207 Moroccan exporting small and medium-sized enterprises (SMEs) and analyzed using SPSS 25 and Structural-equation Modeling with the aid of AMOS 23. Outcomes revealed that CSR has no significant direct effect on FP, but rather an indirect effect through REP and CS. Likewise, the link between CSR and FP is mediated on the one hand by CS and CA, successively and on the other hand by REP and CA, successively. These findings provide a verified theoretical framework for SME managers to plan and execute CSR to enhance FP by indirectly targeting the aforementioned intangible assets. The paper contributes to the knowledge of how CSR practices lead to FP in an under-explored context of SMEs in a developing country.